(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Striga hermonthica (Del.) Benth is an important parasitic weedon cereals in the semi-arid tropics. Intercropping, particularly of cerealswith cowpea (Vigna unguiculata), is a common practice in many parts ofthe semi-arid zone. The main objectives of this study were to determinethe influence of sorghum-legume intercropping on striga control in centralSudan, and to assess the effect of such association on crop performance.Field experiments were conducted in striga-infested plots at theAgricultural Research Corporation (ARC) farm at Wad Madani, Sudan,during the 2009/2010 and 2010/2011 seasons. Sorghum cultivarsArfagadamk and Wad Ahmed were intercropped with four legumes.Treatments were arranged in randomized complete block design with 3replicates. Striga emergence was significantly reduced by 37.7% - 85.6%in sorghum-legume intercropping compared to sole sorghum, irrespectiveof variety and season. The highest reduction in striga emergence wasobtained with the sorghum cv. Arfagadamk-legume intercropping, whichreduced striga emergence by 72.5% - 85.6% compared to sole non-fertilized sorghum. Striga dry weight was high in sole sorghum incomparison with sorghum intercropped with legumes. Sorghum cv.Arfagadamk intercropped with lablab bean, brown-seed cowpea, andwhite-seed cowpea significantly reduced striga dry weight by 95%, 90%,and 73%, respectively. The total biological yield of both sorghumcultivars per unit area was generally higher in the intercropping